Feasibility of in-home electroencephalographic and actigraphy recordings in dogs - Folkard, Emily; McKenna, Charly; Monteith, Gabrielle; Niel, Lee; Gaitero, Luis; James, Fiona May Keir (Frontiers in Veterinary Science, 2024)
Idiopathic epilepsy is a prevalent neurological disease in dogs. Dogs with epilepsy often present with behavioural comorbidities such as aggression, anxiety, and fear. These behaviours are consistent with pre, post, or interictal behaviours, prodromal changes, seizure-precipitating factors, or absence and focal seizures. The overlap in behaviour presentations and lack of objective research methods for quantifying and classifying canine behaviour makes determining the cause difficult. Behavioural comorbidities in addition to the task of caring for an epileptic animal have a significant negative impact on dog and caregiver quality of life. This pilot study aimed to assess the feasibility of a novel technology combination for behaviour classification and epileptic seizure detection for a minimum 24-hour recording in the dog’s home environment. It was expected that combining electroencephalography (EEG), actigraphy, and questionnaires would be feasible in the majority of trials. A convenience sample of 10 community-owned dogs was instrumented with wireless video-EEG and actigraphy for up to 48 hours of recording at their caregiver’s home. Three questionnaires (maximum 137 questions) were completed over the recording period by caregivers to describe their dog’s everyday behaviour and habits. Six of the 10 included dogs had combined EEG and actigraphy recordings for a minimum of 24 hours. This shows that in-home EEG and actigraphy recordings are possible in community-owned dogs and provides a basis for a prospective study examining the same technology combination in a larger sample size.